PENINGKATAN PUBLIC SPEAKING GURU DENGAN NLP (NEURO-LINGUISTIC PROGRAMMING) - Yusufi, Adnan; Muntaqo, Rifqi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2025)
Public speaking is an essential skill for teachers in the field of education. The ability to speak confidently and effectively in front of an audience can significantly influence the quality of teaching and interaction with students. However, many teachers face challenges when speaking in public, such as anxiety, fear of negative evaluation, and lack of self-confidence. These issues often hinder teachers from delivering content effectively, which ultimately impacts the learning process in the classroom. This study aims to examine the application of NLP in improving teachers' public speaking skills. Various NLP techniques are expected to help overcome anxiety, enhance self-confidence, and improve teachers' communication in front of the classroom. This research uses a qualitative approach with a literature study design to analyze relevant literature on the application of NLP in the context of public speaking. The findings indicate that NLP techniques have significant potential in helping teachers improve their public speaking skills. Techniques such as anchoring assist teachers in managing anxiety, rapport building improves relationships with students, and reframing changes negative mindsets into more positive ones. The state management technique allows teachers to manage and alter their emotional states, while submodalities enable them to change their mental representations of speaking situations, thus creating more positive feelings and boosting self-confidence. Additionally, techniques like modeling and well-formed outcome provide clear guidance for improving speaking skills and setting measurable goals in teaching. By mastering these techniques, teachers can overcome various communication challenges, enhance interaction with students, and ultimately create a more productive and enjoyable learning experience.